An analysis of primary school children’s drawings based on Wilsons’ Seven Principles / Yu Lei Tao - Yu , Lei Tao (2021)
Issues about low perception and limited information on children’s drawings in Malaysia has led to the need of analysis of children’s drawings. This study studied and analyzed drawings of a group of Malaysian primary school children of six age groups based on Wilson and Wilson (2009) seven graphic principles. A quantitative research design was adopted. A total of 335 children’s drawings were analyzed to identify the most common used Wilsons’ graphic principle and determine the use of the principles according to their age groups by using descriptive statistic method. In order to determine the relationships between children’s used of Wilsons’ graphic principles and their stage of pictorial development, inferential testing by using Chi-Square was conducted. The findings of this study show that; conservation/multiple application principle was the most common Wilsons’ graphic principle that children used in their drawing, and there were similarities and differences in the use of principles for each children’s age groups. In addition, the Chi-Square test indicated significant association between children’s used of every principles and their stage of pictorial development with all p values ≤ .05. Thus, it can be concluded that children’s artistic development can be established using the Wilson and Wilson seven graphic principles. A continued need exists for further research to be conducted to make comparisons between gender and between cultures.